The impact of changes to the WADA prohibited list on the use of over-the-counter medication by athletes - Chester, N.; Mottram, D.; Atkinson, G.; Goode, D. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The aim of the study was to assess use of over-the-counter (OTC) medication, amongst elite athletes across 10 sports, from four nations, with specific reference to stimulants on the WADA Monitoring Program and Prohibited List. A Questionnaire was developed to assess athletes OTC drugs use, knowledge and understanding of OTC medication with reference to anti-doping measures and views regarding changes to the Prohibited List. Distribution was by traditional and electronic means to elite athletes from Australia, Canada, the UK and the USA representing track and field athletics, canoeing, cycling, gymnastics, hockey, rowing, swimming, triathlon, volleyball and weightlifting. Respondents (n = 557) comprised an equal split of males and females and an 80:20 split in terms of age (§20 years: <20 years). Representation of sports varied from 5.4% (Triathlon) to 17.4% (swimming) and of nations, from 14.1% (Canada) to 39.8% (USA). Two thirds of respondents had been drug tested on at least one occasion. During the preceding 12 months, no athletes reported use of OTC medication containing prohibited substances, but 38% had used OTC medication containing substances that were part of the Monitoring Program. Pseudoephedrine (29.6%) and phenylephrine (9.3%) use was most prevalent. Most athletes used OTC products for therapeutic purposes (73.3%) and a small proportion for their reputed ergogenic properties (3.4%). Overall, athletes demonstrated limited knowledge relating to the penalty incurred following a doping violation involving a banned OTC stimulant; the terms Monitoring Program and Specified Substance; and the prohibitive status of OTC substances. However, if unsure of the prohibitive nature of an OTC product almost all respondents would consult someone for advice, with the WADA and national anti-doping organisations most commonly cited. Young athletes (<20 years) were more likely to consult an individual, such as their coach, training partner or team doctor for advice. Generally, athletes indicated that stimulants in OTC medication were: not performance enhancing; a risk to health; against the spirit of sport; and yet should remain off the Prohibited List. Whilst use of stimulants contained in OTC medication is significant amongst athletes, it is primarily for therapeutic purposes. There is an apparent lack of knowledge and awareness of OTC medication in reference to anti-doping, suggesting that ignorance remains an important factor in their use amongst athletes. This is tempered by their willingness to seek advice from reliable sources. Direct comparisons with the Monitoring Program data were invalid; however there would appear to be disparity in terms of phenylephrine use with laboratory data suggesting negligible use in recent years. The inability of the Monitoring Program to provide valid evidence to support misuse (or otherwise) of substances contained in OTC medications highlights the need to expand the programme and include qualitative assessment.